MENCIPTAKAN PERSAINGAN USAHA YANG SEHAT DI INDONESIA (Analisis Terhadap UU No. 5 Tahun 1999 tentang Anti Monopoli Dan Persaingan Usaha Tidak Sehat) - Santoso, Dri (STAIN Jurai Siwo Metro, 2004)
The constitution of Indonesia gives freedom to each individual to effort and to gain estate for living development and its welfare. The freedom doesnât give positif effect more for Indonesiaâs business world, besides it to encourage the effect of monopoly toward business subjects that give on unhealthy competition.Phenomena above it gives effect to attaining the Indonesiaâs national aim such as creating large prosperity and welfare for Indonesian people. The born of the constitution number 5 year 1999 about resistant of monopoly and unhealthy business competition is an effort to keep the activity of monopolistic and the kind of it. In this constitution is arranged as well business competition supervisor commission that leads to supervise the attitude of business in order not to act monopolistic attitude. The treat of punishment can be given to the business actor who do that attitude beside administrative sanction.Â Â Keyword : business competition, monopoly.